npj Energy Materials - Wang, Donghai; Low, Chew Juan.; SpringerLink (Online service) (London : Nature Publishing Group UK : Imprint: Nature Portfolio.)
npj Energy Materials considers fundamental and applied research on materials for electrochemical energy technologies. Topics covered by the journal include: Energy materials for batteries (lithium-ion, sodium-ion, multivalent-ion, solid-state, and other emerging chemistries), supercapacitors, and fuel cells. Electrocatalysis $1 (Bmaterials and mechanisms for key electrochemical energy conversion, such as oxygen reduction, oxygen evolution, hydrogen evolution, and COb2 (Belectroreduction, etc. Sustainable approaches for recycling, circularity, and life-cycle management of electrochemical energy systems. Modeling and simulation of electrochemical energy systems across atomic, molecular, materials, and device scales. Cross-disciplinary advances in materials design, synthesis, characterization, and system integration relevant to electrochemical energy technologies. The journal offers more choice to Nature Portfolio authors who are seeking a fully open-access and more inclusive platform for publishing their work. The journal is led by materials science and energy technology experts who collaborate to cultivate high-quality research. As part of the npj Series, this journal focuses on fostering global partnerships with the research community and other Springer Nature journals.s
Keywords: Materials; Catalysis; Force and energy; Materials science; Surfaces (Technology).; Thin films; Nanoelectromechanical systems; Nanochemistry; Metals; Materials for Energy and Catalysis; Materials Science; Surfaces, Interfaces and Thin Film; Nanoscale Devices; Nanochemistry; Metals and Alloys